Forest Printing Enterprise / Nureen Azzahra Ahmad Faizal ... [et al.] - Ahmad Faizal, Nureen Azzahra; Adam, Siti Nur Syazreen; Ahmad Rasidi, Anis Syafiqah; Zaidi, Rabiatul Anis; Saiful Adli, Humairah (2022)
First of all, Forest Printing Enterprise is a T-shirt printing company that offers custom-made printed design on the shirt. Our goals and aim is to provide our customers with a professional, service that is always fair, efficient, helpful and responsive in providing the customer demand. Furthermore, we hope to develop a strong and creative printing company that can satisfy customer’s request. Also, our target market is following by demographic segmentations which is age base on 18 years old until 55 years old according to the population. This printing business is located in Georgetown, Pulau Pinang that are in the city center, which is strategic location, we can easily attract the customers who wanted to use our services and we attract them by using our signboard sign. Forest Printing Enterprise logo and name represent the Flora and Fauna nature, also with the illustrations of the hands that holds the painting brush are the symbol of we make a custom-made T-shirts. As we know from then until now, business printing is needed by all parties. This is because everyone wants to make their own merchandise and clothes. For example, for employees in any workplace, the company of the place would make sure their uniform are same with each other. In addition, according to the current market trend business printing is very much the talk of the set of the community. Moreover, the capital of the company is contributed by five partners of the organization including the general manager, Administration manager, Marketing manager, Operational manager and lastly is financial manager of this business. The partner of this business was chosen for their own experience and educational background. In this Printing Shop we provide a spacious waiting area for the customer to wait for the staff to attained them for the custom design process. However, we also provide the pantry for the staff and also the customer to have a drink. Finally in this Forest Printing Enterprise, we hope that this business can be well known in Malaysia. We can achieve our aims and target by launching and starting this business and to be more successful and be known in the future by this business